Cooperative functioning of salicylic acid and phenylalanine ammonia lyase in barley plant challenged with spot blotch and powdery mildew diseases - Al-Daoude, Antonious; Al-Shehadah, Eyad; Shoiab, Amina; Jawhar, Mohammed; Arabi, Mohammed Imad Eddin (Acta Biologica Szegediensis, 2019)
Salicylic acid (SA) and phenylalanine ammonia-lyase (PAL) have been suggested as important signals during plant resistance towards several fungal pathogens. In this work, to better understand the defense responses initiated by resistant and susceptible barley genotypes challenged with a necrotrophic (Cochliobolus sativus; Cs) and a biotrophic (Blumeria graminis; Bg) pathogens, the relative contributions of SA and PAL were investigated at early time points of infection. SA signaling was activated in both genotypes 24 hours post infection (hpi) as compared with the non-inoculated plants. However, with or without pathogen pretreatment, SA significantly increased (P = 0.001) in the resistant genotype that contained three-folds of total SA in comparison with the susceptible one for Bg. Reverse transcription-polymerase chain reaction (RTPCR) analysis revealed that PAL expression increases in the resistant and susceptible genotypes over the inoculation time points, with the maximum expression observed 48 hpi. PAL expression was paralleled by an increase in SA content in leaves as shown by the test coincidence (F3, 32 = 1.09, P = 0.49 for Cs and F3, 32 = 1.03, P = 0.48 for Bg). Results showed that the cooperatively function of SA and PAL in barley responses to both Cs and Bg appeared to be dependent on the plant genotype, and that SA signaling and PAL play a role in barley interactions with these both pathogens. This study might increase our understanding for a deeper molecular research on barley defense responses against pathogens with different lifestyles.